Imaging dynamic pore-formation processes in droplet-interface bilayers - Sengel, JT (2017)
Observing dynamic pore-forming processes in lipid bilayers is a challenging task. It requires a bilayer system that is stable, compositionally adjustable, and one that may be interrogated using electrical and optical techniques. Aside from these practical challenges, and that pore formation is inherently destructive to the bilayer system, membrane pores are often highly transient, with milli- or microsecond lifetimes, and are seldom larger than a few tens of nanometres in diameter.